Optimal preservation investment, pricing and ordering policies for deteriorating inventory with trapezoidal demand. (2016) - Shah, Nita H.; Shah, Digeshkumar B.; Patel, Dushyantkumar G.
Each product has its own life span and as time progresses the product deteriorates as per its nature. Companies are concerned about this deterioration and take actions to reduce it by deploying some preservation technologies. In market, demand for some items increases initially, stabilises and then decreases severely. Such demand is named as trapezoidal demand which is analysed in the present article. Preservation technology investment plays a vital role in the profit of the firm. Cycle time and retail price are the basic factors that affect profit. So, maximum profit is achieved with respect to optimal investment made, sale price of unit and procurement quantity. Numerical examples and related graphical studies are presented to validate the results. Effects of variations in inventory parameters on profit are shown to take beneficiary decisions.